2021
DOI: 10.1002/aelm.202000870
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecules with Controllable Molecular Weights Passivate Surface Defects in Air‐Stable p‐i‐n Perovskite Solar Cells

Abstract: The passivation of surface defects at the interfaces and grain boundaries of perovskites has great potential to improve the optoelectronic properties of related devices. In this study, the small molecules LG0.5, LG1.5, and LG2.5—having precise and controllable molecular weights (various generations synthesized through click reactions) and featuring urethane, urea, and malonamide functionalities—are synthesized, and their ability to passivate the defects of perovskites are evaluated. X‐ray photoelectron spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…For example, organic materials containing S, N, O and P atoms can work as Lewis bases to passivate the positively charged defects, such as under-coordinated Pb 2+ in perovskites. [27][28][29][30][31][32][33][34] Some highly polarized small molecules or polymers with carboxylic acid groups are also proved to be efficient passivators to modify the bulk or surface of perovskite thin films. 35,36 Zwitterionic materials are a class of unique electrolytes, where both cationic and anionic moieties are covalently tethered on the same chain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, organic materials containing S, N, O and P atoms can work as Lewis bases to passivate the positively charged defects, such as under-coordinated Pb 2+ in perovskites. [27][28][29][30][31][32][33][34] Some highly polarized small molecules or polymers with carboxylic acid groups are also proved to be efficient passivators to modify the bulk or surface of perovskite thin films. 35,36 Zwitterionic materials are a class of unique electrolytes, where both cationic and anionic moieties are covalently tethered on the same chain.…”
Section: Introductionmentioning
confidence: 99%
“…The synergistic effect between functional groups known as synergistic passivation was studied to enhance this passivation. Synergistic passivation refers to the passivation effect produced by the simultaneous action of molecules or functional groups. ,, Chemical interactions commonly used for passivation include Lewis coordination, hydrogen bond, and electrostatic interaction, and there has been some progress in the study of synergistic passivation. Recently, Wang et al found that the hydrogen bond between N–H and I can enhance the coordination passivation of the CO bond with the antisite Pb defect .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic NiO x - and CuO x -based thin films are also widely used in the inverted perovskite solar cells as the HTL [ 41 , 42 ]. The photovoltaic performance of NiO x -based inverted perovskite solar cells can be increased to be higher than 20% by using an organic interlayer in between the perovskite thin film and the HTL [ 43 , 44 , 45 , 46 , 47 ]. In other words, the formation of high-quality perovskite crystalline thin films is not only related to the surface wettability [ 48 , 49 , 50 ] but is also dominated by the nucleation process of perovskites on top of the organic layers.…”
Section: Introductionmentioning
confidence: 99%